PENANAMAN DAN PEMBENTUKAN KARAKTER SISWA MELALUI PERMAINAN TRADISIONAL RIMAU LANGKAT - Nuraida Nuraida; Daulat Saragi (LP3M INSTITUT KH YAZID KARIMULLAH, 2023)
As a historical heritage, the traditional game of rimau langkat is very difficult to find. The development of the 4.0 revolution era, this game is already difficult to find, because the current era of traditional things has shifted towards digital and has been little practised and played by children. This study intends to instil student character through the traditional game of rimau langkat. As the object of study, the traditional game of rimau langkat has a crucial role in instilling and shaping student character. This study aims to revitalise traditional games. This study is a qualitative study using field studies and literature studies to collect data. The study will be conducted at SDN 057224 Paluh Gusta and the result of this study is that the traditional game of rimau langkat is able to instil and shape the character of good students and show positive things, it can be seen from the ability of students to respect each other, socialise with friends, and be innovative and creative.